2018
DOI: 10.1002/jmri.25977
|View full text |Cite
|
Sign up to set email alerts
|

Free‐breathing dynamic contrast‐enhanced MRI for assessment of pulmonary lesions using golden‐angle radial sparse parallel imaging

Abstract: 2 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2018;48:459-468.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…The radial sampling scheme enables continuous data acquisitions during free breathing; the combination of compressed sensing and parallel imaging enables high temporal resolution and spatial resolution for different dynamic imaging applications; and, more importantly, the golden‐angle radial sampling scheme allows a dual‐mode reconstruction strategy that can be used for both morphological qualitative assessment and quantitative perfusion analysis simultaneously. The performance of GRASP has been demonstrated in a range of clinical applications, and it has recently been extended to free‐breathing DCE‐MRI of the lung for assessment of pulmonary lesions . These preliminary studies have all shown the great potential and capabilities of GRASP for improving the usefulness and effectiveness of DCE‐MRI towards routine clinical use.…”
mentioning
confidence: 99%
“…The radial sampling scheme enables continuous data acquisitions during free breathing; the combination of compressed sensing and parallel imaging enables high temporal resolution and spatial resolution for different dynamic imaging applications; and, more importantly, the golden‐angle radial sampling scheme allows a dual‐mode reconstruction strategy that can be used for both morphological qualitative assessment and quantitative perfusion analysis simultaneously. The performance of GRASP has been demonstrated in a range of clinical applications, and it has recently been extended to free‐breathing DCE‐MRI of the lung for assessment of pulmonary lesions . These preliminary studies have all shown the great potential and capabilities of GRASP for improving the usefulness and effectiveness of DCE‐MRI towards routine clinical use.…”
mentioning
confidence: 99%
“…Radial sampling scheme so-called stack-of-stars technique is also promising [8,9]. By monitoring the respiratory movement from the k-space data, stack-of-stars technique may be able to avoid artifact due to abdominal wall motion [10].…”
mentioning
confidence: 99%
“…Indeed, lung MRI suffers from the very fast decay of the lung signal related to susceptibility artifacts, the low proton content, and the need of synchronization due to cardiac and respiratory motions . Recent advances in the use of ultrashort echo time (UTE) has been able to improve pulmonary MR image quality in 3D . An increase in signal and contrast was shown in both healthy volunteers and patients with pulmonary diseases, from neonate to adulthood .…”
mentioning
confidence: 99%
“…Although all 3D sequences seek to decrease the echo time down to the microsecond, variable schemes are used to sample the k ‐space. The two main k ‐space variants consist in acquiring the k ‐space either radially into a sphere or into a cylinder using stack‐of‐discs such as stack‐of‐stars or stack‐of‐spirals . In our institution, a novel prototype dedicated to 3D‐UTE imaging using VIBE (volume interpolated breath‐hold examination) and stack‐of‐spirals (3D‐USV) has been released for testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation